Acupuncture for arousal combined with repetitive transcranial magnetic stimulation promotes functional reorganization of brain regions in patients with a minimally conscious state: study protocol for a randomized controlled trial - Li, Jiajia; Fang, Hongjing; Liu, Tong; Li, Peixin; Ou, Zhihong; Li, Zhihui; Huang, Tao; Sun, Juan; Zhang, Jueyu; Lu, Fangyi; Wen, Xi (Frontiers in Neurology, 2025)
IntroductionThe minimally conscious state (MCS) is one of the common and serious complications of stroke patients. Its incidence is higher than that of other types of consciousness disorders. The prolonged monitoring and comprehensive management of patients with MCS imposes substantial socioeconomic burden, creating multifaceted challenges for healthcare systems and considerable strain on familial resources. However, there are still few studies on the treatment of MCS, so there is a lack of standardized and effective treatment for MCS, which needs to be solved urgently. In order to solve this problem, this study proposes a treatment plan of acupuncture for arousal combined with repetitive transcranial magnetic stimulation (rTMS). Acupuncture for arousal is a clinical acupuncture therapy. Accumulating evidence from the published literature indicates that acupuncture for arousal interventions can significantly enhance consciousness levels in comatose patients. Nevertheless, conventional acupuncture monotherapy necessitates extended treatment durations, potentially compromising patient outcomes and neurological recovery trajectories. rTMS can excite or inhibit specific cortical functional areas of the brain, thereby improving the level of consciousness in comatose patients. The significance of this study is to clarify the efficacy and safety of wake-promoting acupuncture combined with repetitive transcranial magnetic stimulation in patients with minimal consciousness after stroke, and to add a standardized and effective scheme for the treatment of MCS. Furthermore, this investigation employs neural-specific biomarkers and functional magnetic resonance imaging to elucidate the mechanisms underlying regional brain functional reorganization. These neuroimaging and molecular approaches may establish a robust scientific foundation for future investigations into consciousness-restoring mechanisms in patients with MCS.Methods and analysisThis is a single-center design, randomized, controlled, third-party blind trial involving 117 patients. Three groups of patients will receive 4 weeks of treatment. Under basic treatment, the acupuncture for arousal group will only receive acupuncture treatment. The rTMS group only receives rTMS treatment; the combined group is treated with the acupuncture for arousal and rTMS. The main outcome indicators are the GCS score scale, the CRS-R score scale, central nerve-specific protein (S-100B), neuron-specific enolase (NSE), and functional magnetic resonance imaging (fMRI). The secondary outcome indicators are laboratory safety parameters, including routine blood tests, routine urine tests, coagulation tests, electrocardiograms, liver function tests, and renal function tests. Finally, the measurement data and enumeration data will be analyzed via SPSS 25.0 software.Ethics and disseminationThis study has been approved by the Ethics Committee of the Second Chinese Medicine Hospital of Guangdong Province (Approval No.: K202405-003-01, June 19, 2024). The research results will be published in peer-reviewed journals.Clinical trial registrationhttps://www.chictr.org.cn/bin/project/edit?pid=235202, ChiCTR2400086163.